Model Analysis Principles for the Design of Public Spaces in Bistrița-Târgu Mureș Urban Axis - TĂTAR, Alexandru Marius (Studia Universitatis Babeș-Bolyai Geographia, 2024)
Model Analysis Principles for the Design of Public Spaces in the Bistrița-Târgu Mureș Urban Axis. The physical urban terrain across cities continually evolves through insights, consultations, deliberate redesigning or random acts by community members and natural forces that reshape the urban landscapes and how urban spaces are used. This research establishes a set of normative principles that planners and others can use when planning and regulating the design and management of public space. Data were collected in the period March 2023 – January 2024. Based on a comprehensive analysis of public space in the city, the paper sets out a number of general principles relating to the essential, but often missing, strategic planning framework for developing and regenerating public spaces, providing seven more detailed considerations for assessing the quality of public space design and a proposal for spatial planning. This is an unreservedly positive framework for shaping public space, based on the idea that public spaces in our cities come in many different shapes and forms, but that together they add immense value to the experience and potential of urban areas. The research takes place in the Bistrița-Târgu Mureș urban axis, the field research carried out as part of the study results in a set of three principles of urban spatial planning that examine proposals for the design of public spaces.